2008
DOI: 10.1177/145749690809700111
|View full text |Cite
|
Sign up to set email alerts
|

Introducing an Asymmetric Cleft Lift Technique as a Uniform Procedure for Pilonidal Sinus Surgery

Abstract: Background and Aims: asymmetric techniques for surgery in pilonidal sinus disease (psd) have been reported to provide better results than simple excision and closure in the midline. the aim of this retrospective study was to evaluate the results after introducing the Bascom asymmetric cleft lift procedure in our hospital on aday care basis.Material and Methods: from atotal of 33 patients operated from april 2002 to september 2004 with the Bascom asymmetric cleft lift technique, we were able to contact 29 who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
2
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
(4 reference statements)
0
14
2
13
Order By: Relevance
“…Studies have shown it to be excellent in refractory cases of pilonidal disease [5,12]. There is a growing community of adult general and colorectal surgeons who believe that the cleft lift procedure is one of the preferred techniques in treating moderate and severe chronic and refractory pilonidal disease [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown it to be excellent in refractory cases of pilonidal disease [5,12]. There is a growing community of adult general and colorectal surgeons who believe that the cleft lift procedure is one of the preferred techniques in treating moderate and severe chronic and refractory pilonidal disease [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Operative procedures such as Limberg flap, Karydakis flap, fasiocutaneous V-Y advancement flap reconstruction and Cleft lift procedure are used in recurrent and complicated disease. High rates of success was obtained for the treatment of recurrent disease with these surgical procedures [12][13][14][15]. Besides this, several minimally invasive methods are also available such as laser hair removal and crystallized phenol application and these methods can be applied in postoperative recurrence of pilonidal disease [10,16].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the promising early results, they concluded that Bascom procedure can be the standard procedure for chronic pilonidal sinus disease. 12 In this debate of primary closure of defect after surgical excision whether midline or off midline closure, Nessar et al advised extensive excision of the pilonidal disease up to sacral fascia and closed these defects off midline using an elliptical cutaneous rotation flap. These patients were discharged on first postoperative day.…”
Section: Discussionmentioning
confidence: 99%